The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cbf.3356
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ABCD2 dysregulates lipid metabolism via dysregulation of miR‐141:ACSL4 in human osteoarthritis

Abstract: Even though increasing evidence indicates the importance of peroxisomal lipid metabolism in regulating biological and pathological events, its involvement in cartilage development has not been well studied. Here, we identified the importance of peroxisomal function, particularly the functional integrity of ABCD2, in the pathogenesis of osteoarthritis (OA). Knockdown of ABCD2 in OA chondrocytes induced the accumulation of very long chain fatty acids (VLCFAs) and apoptotic cell death. Moreover, knockdown of ABCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…One recent study by Park et al . reported the dysregulated miR-141-3p through ATP‐binding cassette transporter in human OA chondrocytes participated in altered lipid metabolism and suggested a novel insight into understanding the pathogenesis of OA 49. In view of inflammatory conditions, miR-141 seemed to play dual roles in regulating inflammation-related signaling pathways.…”
Section: Discussionmentioning
confidence: 97%
“…One recent study by Park et al . reported the dysregulated miR-141-3p through ATP‐binding cassette transporter in human OA chondrocytes participated in altered lipid metabolism and suggested a novel insight into understanding the pathogenesis of OA 49. In view of inflammatory conditions, miR-141 seemed to play dual roles in regulating inflammation-related signaling pathways.…”
Section: Discussionmentioning
confidence: 97%
“…Also, lipid metabolism is a chemical reaction involving lipids, which are compounds soluble in organic solvents [66]. Park et al showed that the functional integrity of ABCD2 in modulating lipid metabolism was through the dysregulation of miR-141, and through ACSL4 in OA [67].…”
Section: Discussionmentioning
confidence: 99%
“…Among the topstream regulators identified in our ontology analysis was PITX2, a component of the Wnt signaling pathway key to mensenchymal stem cell function which is altered in OA patients 50 . MicroRNA-141 is dysregulated in human OA and contributes to pathogenesis by augmentation of lipid metabolism 51 , and is important in maintaining the appropriate expression of key osteoblast differentiation proteins including Runx2, Sclerostin, ALP, and Dlx5 52 . MicroRNA-9 has been shown to directly augment the expression of the key catabolic enzyme matrix metalloproteinase-13 (MMP13) in OA patients 53 and animal models 54 .…”
Section: Discussionmentioning
confidence: 99%